Laparoscopic hernia repair - Mishra, R.K.; Clarke, John M. (India : Jaypee Brothers Medical Publisher, 2013)
Laparoscopic hernia repair is a relatively new surgical technique to fix tears in the abdominal wall using small incisions, a patch and special cameras to view inside the body. It frequently offers a more rapid recovery for the patient, less postoperative pain, and a quicker return to work and normal activities. (LapSurg.org). This concise guide discusses the latest procedures in laparoscopic hernia repair. Beginning with chapters on the history of hernia, imaging and equipment, the following sections discuss surgical procedures for different types of hernia. Nearly 400 colour images and illustrations are included, as well as two DVD ROMs demonstrating different laparoscopic procedures and discussing potential complications.
1. History of Hernia 2. Laparoscopic Imaging Systems 3. Laparoscopic Equipment and Instruments 4. Laparoscopic Tissue Approximation Techniques and the Art of Endosuturing 5. Prosthetic Mesh Material 6. Laparoscopic Transabdominal Preperitoneal (TAPP) Repair of Inguinal Hernia 7. Totally Extraperitoneal (TEP) Hernia Repair 8. Laparoscopic Repair of Recurrent Inguinal Hernias 9. Laparoscopic Repair of Ventral Hernia 10. Laparoscopic Repair of Hiatal Hernia
Incluye índice
Incluye contenido
Incluye bibliografía
Keywords: LAPAROSCOPIC HERNIA REPAIR; LAPARASCOPIA